THE RELATIONSHIP BETWEEN LOCUS OF CONTROL AND SELF-CONCEPT WITH LEARNING ACHIEVEMENT OF STUDENTS AT STATE VOCATIONAL SCHOOL 51 JAKARTA - Dira Nurmawati (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
The purpose of this research is to determine the correlation between locus of control and self-concept with learning achievement in students at SMK Negeri 51 Jakarta. This research was conducted at SMK Negeri 51 Jakarta for 6 months, starting from January to June 2018. The method used was a survey method with a correlational approach. This study uses a population of all class XI students at SMK Negeri 51 Jakarta. The sampling technique is a simple random technique with 127 students. Based on the results of the analysis and discussion it is known partially that there is a positive and significant relationship between locus of control and student achievement, there is a positive and significant relationship between self-concept and student achievement.